Additional file 5 of Revisiting chloroplast genomic landscape and annotation towards comparative chloroplast genomes of Rhamnaceae - Kwanjeera Wanichthanarak; Intawat Nookaew; Phongthana Pasookhush; Thidathip Wongsurawat; Piroon Jenjaroenpun; Namkhang Leeratsuwan; Songsak Wattanachaisaereekul; Wonnop Visessanguan; Yongyut Sirivatanauksorn; Narong Nuntasaen; Chutima Kuhakarn; Vichai Reutrakul; et al. (My University, 2023)
Additional file 5: Table S7. Changes of amino acids from RNA editing
Keywords: Rhamnaceae; Phylogenomics; Genomics and Phylogenetic Studies